2020
DOI: 10.1016/s2666-5247(20)30007-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and drivers of false-positive rifampicin-resistant Xpert MTB/RIF results: a prospective observational study in Rwanda

Abstract: Background The Xpert MTB/RIF (Xpert) assay is used globally to rapidly diagnose tuberculosis and resistance to rifampicin. We investigated the frequency and predictors of false-positive findings of rifampicin resistance with Xpert.Methods We did a prospective, observational study of individuals who were enrolled in a Rwandan nationwide diagnostic cohort study (DIAMA trial; NCT03303963). We included patients identified to have rifampicin resistance on initial Xpert testing. We did a repeat Xpert assay and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 27 publications
8
48
2
2
Order By: Relevance
“…However, in agreement with the previous study 11 , in our study the high pretest probability of RR did not lower the rates of false resistance as there were almost half of patients previously treated who had no RR detected on repeat Xpert. Some studies have associated the discordance of Xpert for RR due to low bacterial load clinical specimens 11,15 . In our study, 7/15 (46.7%)of the TB patients with discordant RR results had very low bacterial load on the initial Xpert test ( Table 2).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, in agreement with the previous study 11 , in our study the high pretest probability of RR did not lower the rates of false resistance as there were almost half of patients previously treated who had no RR detected on repeat Xpert. Some studies have associated the discordance of Xpert for RR due to low bacterial load clinical specimens 11,15 . In our study, 7/15 (46.7%)of the TB patients with discordant RR results had very low bacterial load on the initial Xpert test ( Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…The burden may be underestimated since among the 29 repeat Xpert MTB not detected patients, eight were culture positive of which 4 (50%) had RR-TB not detected. A recent study in Rwanda found high levels of false RR, after repeat, attributed to low bacillary load samples 11 . In our study, 7/15 (46.7%) patients with false Xpert RR had very low bacillary load on the initial Xpert.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of nucleic acid-based tests like CBNAAT has provided novel avenues for generating highly sensitive point-of-care tests but still has significant limitations in diagnostic accuracy for DR TB. [12] Our study found that DR TB was more common among relapse cases. These findings corroborated with earlier studies which also substantiated that drug-resistant TB was more common among relapse cases than freshly detected TB cases.…”
Section: Discussionmentioning
confidence: 51%
“…Previously diagnosed drug-resistant Pulmonary TB by sputum CBNAAT having constitutional symptoms but not on any ATT for a minimum of two months duration, who reported at DOTS center for routine follow up were also included in the study. where P = Expected prevalence or proportion, d = precision and Z = statistic for level of confidence ( in our case 1.96 as per 95 % CI ), using the test sensitivity as 92% and specificity 95% (12). The calculated sample size was 186.…”
Section: Methodsmentioning
confidence: 99%